The Politics of Business in the Economic "Grossraum": The Example of Belgium - Gillingham, John (Studia Historiae Oeconomicae, 1979)
This paper explores the role of Belgian business elites in integrating Belgium’s economy into Nazi Germany’s wartime economic Grossraum (greater economic area). The background centers on the German occupation of Belgium during World War II and Hitler’s broader goal of transforming Europe into a resource base for the Nazi war machine. The Reich sought to extract maximum material value from occupied territories to sustain its war effort, particularly after military setbacks in 1941–1942. The aim of the study is to analyze how Belgian business leaders – especially those from dominant holding companies like Société Générale de Belgique – collaborated with German authorities to maintain domestic control in exchange for cooperation with German war production. The article focuses on the "Politics of Production," a policy that offered internal autonomy in return for fulfilling Reich military needs. The Galopin Committee, composed of Belgium’s top industrialists, was instrumental in shaping and directing this policy. The analysis is based on a wide range of sources, including occupation records, economic directives, business correspondence, and postwar tribunal documents. It details how Belgian industry was structurally and financially reorganized to meet German demands, with key roles played by German banks such as Deutsche Bank and industrial actors from the Ruhr. Key findings reveal a pragmatic collaboration: Belgian business preserved its internal authority and financial interests, while Germany secured critical resources and production. The arrangement was enabled not by ideological alignment but by mutual economic benefit. Nonetheless, internal conflicts within German economic policy – between plunder and partnership – exposed the fragility of the system. Ultimately, Belgium's contribution to the Nazi war economy was substantial, but the economic order rested on fragile cooperation rather than totalitarian control.